Fruit production under different environmental and management conditions of argan, Argania spinosa (L.) - Zunzunegui, M; Ain-Lhout, F; Jáuregui, J; Díaz Barradas, M C; Boutaleb, S; Álvarez-Cansino, L; Esquivias, M P (Journal of Arid Environments, 2010)
The study’s aim was to evaluate the effects of different management and environmental conditions on fruit and seed mass production of Argania spinosa, an endemic tree to Morocco that grows in arid and semiarid areas and is now undergoing a protracted regression due to overexploitation. Four study areas with different herbivory intensity, altitude and climatic conditions were selected. In each one the following measurements were carried out in 20 trees: tree and crown height, crown projection, trunk diameter, leaf area index, tree density, fruit production$m3 , number of fruits per tree, fruit, endocarp and kernel mass and seed size. The greatest fruit production and fruit size were found in populations with better climatic conditions, followed by the population under high human pressure. The lowest fruit production and fruit size were found in the population under the most severe climate conditions. Mean kernel mass was not affected by harsh climatic conditions or high human pressure, but when both stressing factors were combined all measured fruit traits were abated. Although A. spinosa is tolerant to high herbivory pressure, this perturbation induces a drastic decrease in fruit production. Managing plans addressing its reintroduction and/or maintenance should include a conservative strategy controlling herbivory
Keywords: herbivory; Kernel mass; leaf area index; Oil content; Oil production; seed mass

Long-term transpiration change with rainfall decline in a Mediterranean Quercus ilex forest - LIMOUSIN, J. M.; Rambal, S.; OURCIVAL, J. M.; Rocheteau, A.; JOFFRE, R.; RODRIGUEZ-CORTINA, R. (Global Change Biology, 2009)
In the Mediterranean basin, precipitation is expected to decline as a consequence of climate change. The response of a Quercus ilex forest in southern France to such a decline in water availability was studied using a 4-year throughfall exclusion experiment. Seasonal courses of sap flow and leaf water potential were obtained from 2004 to 2007 and used to characterize tree water relations in a control and a dry treatment. The experiment reduced the average precipitation input to the soil by 29%, and resulted in a 23% reduction in annual transpiration. Soil water potential was significantly lower in the dry treatment only during summer drought, but transpiration was reduced all year round even during well-watered periods. Despite a tight stomatal control over transpiration, whole-tree hydraulic conductance was found to be lower in the trees growing in the driest conditions. This reduction in water transport capacity was observed jointly with a reduction in leaf transpiring area. Canopy leaf area decreased by 18% in the dry treatment as a consequence of the throughfall exclusion, which was found to validate the ecohydrological equilibrium theory.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought; ecohydrology; Hydraulic conductance; leaf area index; leaf water potential; Mediterranean evergreen forest; Quercus ilex; throughfall exclusion; Transpiration

Effect of thinning on LAI variance in heterogeneous forests - Davi, H.; Baret, F.; Huc, R.; Dufrêne, E. (Forest Ecology and Management, 2008)
Leaf Area Index (LAI) is a main variable controlling carbon and water ﬂuxes. This paper estimated the effect of thinning on the spatial distribution of leaf area in French forests. While many studies have focused on average LAI, we estimated clumping and measured both average LAI and the variation around it. LAI was derived from digital hemispherical photos at three sites: an unmanaged Fagus sylvatica forest in temperate area (control site), a mixed Mediterranean forest of Quercus ilex and Pinus halepensis, and regeneration of F. sylvatica under a mature stand of Pinus nigra in mountainous area. LAI measurements were also made with LAI 2000 devices over 5 years (from 1994 to 1998) within forest stands dominated by either beech (F. sylvatica L.), by oaks (Quercus petraea (Matus) Liebl., Quercus robur(Matus) Liebl.), or by Scots Pine (Pinus sylvestris L.). Thinning led to a variable decrease in LAI. The coefﬁcient of variation of LAI (CVLAI ) provided a useful ecological index of the level and type of thinning. For undisturbed stands, CVLAI varied from 10% to 20%, corresponding to the higher average LAI values. Disturbances created by thinning increase LAI spatial variability, resulting in larger CVLAI values for all stands considered. Possible explanations of these results and use in remote sensing were discussed.
Keywords: Ecological index; Ecosystem trait; Forest disturbance; forest ecosystems; heterogeneity; leaf area index; thinning

Effect of thinning on LAI variance in heterogeneous forests - Davi, H.; Baret, F.; Huc, R.; Dufrêne, E. (Forest Ecology and Management, 2008)
Leaf Area Index (LAI) is a main variable controlling carbon and water ﬂuxes. This paper estimated the effect of thinning on the spatial distribution of leaf area in French forests. While many studies have focused on average LAI, we estimated clumping and measured both average LAI and the variation around it. LAI was derived from digital hemispherical photos at three sites: an unmanaged Fagus sylvatica forest in temperate area (control site), a mixed Mediterranean forest of Quercus ilex and Pinus halepensis, and regeneration of F. sylvatica under a mature stand of Pinus nigra in mountainous area. LAI measurements were also made with LAI 2000 devices over 5 years (from 1994 to 1998) within forest stands dominated by either beech (F. sylvatica L.), by oaks (Quercus petraea (Matus) Liebl., Quercus robur(Matus) Liebl.), or by Scots Pine (Pinus sylvestris L.). Thinning led to a variable decrease in LAI. The coefﬁcient of variation of LAI (CVLAI ) provided a useful ecological index of the level and type of thinning. For undisturbed stands, CVLAI varied from 10% to 20%, corresponding to the higher average LAI values. Disturbances created by thinning increase LAI spatial variability, resulting in larger CVLAI values for all stands considered. Possible explanations of these results and use in remote sensing were discussed.
Keywords: Ecological index; Ecosystem trait; Forest disturbance; forest ecosystems; heterogeneity; leaf area index; thinning

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization

An examination of the interaction between climate, soil and leaf area index in a Quercus ilex ecosystem - Hoff, Corine; Rambal, Serge (Ann. For. Sci., 2003)
In Mediterranean-type ecosystems, water availability is one of the most significant variables that regulates whole plant leaf area. An equilibrium should exist between climate, soil and leaf area in such water-limited conditions. The aim of this study was to identify the relations between leaf area index (LAI), environment (climate, soil) and fluxes (water, carbon) in Mediterranean evergreen oak (Quercus ilex L.) ecosystems. To achieve this objective, 50-years simulations were performed using the FOREST-BGC model by varying LAI for a reference site and for different climates and soil water holding capacities (SWC). Transpiration, drought stress, net photosynthesis and canopy water use efficiency (WUE) were examined on a yearly basis for the last ten years of the simulation. Similar to other findings, our results show that LAI depends on site water availability, including both climate (precipitation, potential evapotranspiration) and soil factors (e.g. water storage capacity). Low SWC limit the development of the ecosystem. On high SWC soils, development is mainly limited by the climate. When LAI increases under constant SWC and climate conditions, the decrease in annual transpiration per unit of LAI is accompanied by an increase in drought stress. Equilibrium LAI maximizes carbon assimilation. For the reference site, the equilibrium LAI is close to the observed value, 3.25. The corresponding transpiration, assimilation and WUE are 375 mm, 1251 g C m -2 and 3.1 mmol CO 2 mol -1 H 2O, respectively. For the different sites, there is an hyperbolic decline of WUE with increasing SWC. This implies that production efficiency per unit leaf area is higher in most water-limited environments. Our study shows that a model such as FOREST-BGC allows inter-relations between water balance, carbon balance and drought stress to be taken into account to better understand ecosystem LAI.
Keywords: climate; evergreen oak; hydrological equilibrium; leaf area index; mediterranean-type ecosystem; Quercus ilex L.; soil factor; Water availability

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Adaptation and local validation in a Mediterranean environment of a process-level ecosystem model driven by remotely sensed inputs - Lacaze, B; Tabarant, F; Rambal, S (REMOTE SENSING `96: INTEGRATED APPLICATIONS FOR RISK ASSESSMENT AND DISASTER PREVENTION FOR THE MEDITERRANEAN, 1997)
A process-level ecosystem model (FOREST-BGC) has been used to simulate the short-term variability of functional processes and the slower responding allocation of photosynthesis products to plant components maintenance or growth, and to decomposition. The model emphasises Leaf Area Index (LAI) as a key structural attribute with substantial control over ecosystem process rates. Model simulations (soil water balance, photosynthesis, net primary production,...) have been obtained for a 10 years period (1984-1993) and partially validated with ground measurements from an experimental test site located in Southern France (dominant species: holm oak). Further work include scaling up from local to regional level, using remote sensing inputs and ancillary data.
Keywords: funtional processes; Holm oak; leaf area index; model simutalins; photosynthesis alocation; structural attribute

Local variations of ecosystem functions in Mediterranean evergreen oak woodland - Joffre, R; Rambal, S; Romane, F (Ann. For. Sci., 1996)
The spatial variation of ecosystem function was studied in a Quercus ilex coppice growing on hard limestone with low soil water availability. Spatial structures obtained from data on i) leaf area index, ii) leaf litterfall, and iii) leaf litter decay rate were compared. All these variables were sampled on 26 points located within a 30 x 30 m plot. Mean average leaf litterfall over 10 years (1984-1993) was 254 g.m-2. For each year, the semivariograms of leaf litterfall have been fitted using a spherical model. The values of the range parameter (indicating the limit of the spatial dependence) ranged from 6.4 to 10.3 m, very close to the value (9.2 m) of the range parameter obtained when fitting the semivariogram of mean leaf litterfall over 10 years. This result indicates the temporal persistence of the spatial pattern of leaf litterfall. The leaf area index (LAI) was estimated at the same points with a plant canopy analyzer. The mean value was 2.96 ± 0.30. The limit of spatial dependence for LAI was very close to that obtained for leaf litterfall (range = 8.5 m). The litter decomposition pattern was obtained through analysis of litter samples taken at the same points. The percentage of ash-free litter mass remaining (LMR) estimated using near-infrared reflectance spectroscopy indicates the stage of decomposition. It decreased strongly between the surface (mean value 85.6%) and the subsurface layers (mean value 63.4%). The two semivariograms can be described by spherical models, the sill being reached at a range of 21.4 and 18.7 m for the surface and subsurface layers, respectively. The two variables directly related to the structure of the canopy (LAI and leaf litterfall) exhibited close spatial dependence and differed from the soil process-related variables (stage of decomposition) whose ranges were approximately double. These geostatistical analyses show promise for use in developing hypotheses concerning the spatial scale of process-pattern interactions.
Keywords: decomposition; geostatistics; leaf area index; litterfall; local variation; Quercus ilex

STRUCTURAL AND ECOPHYSIOLOGICAL PLASTICITY OF SOME EVERGREEN SPECIES OF THE MEDITERRANEAN MAQUIS IN RESPONSE TO CLIMATE - Gratani, L (PHOTOSYNTHETICA, 1995)
The most representative evergreen shrub species growing in the low mediterranean maquis modified their leaf characteristics during the year, but the response to climate varied among the species. The real sclerophyllous species, Quercus ilex L., Phillyrea latifolia and Pistacia lentiscus, showed a convergence in higher leaf thickness and lower, net photosynthetic rate (PN) compared with Arbutus unedo L. and Cistus incanus L. Under summer stress they maintained a substantial positive carbon balance. Pistacia was one of the most tolerant species to the drought, it maintained a substantial positive balance over a wide range in temperature. Arbutus and Cistus had relatively thin leaves with a higher succulence index and higher PN over the more characteristic sclerophyllous species. The superiority of Cistus in carbon uptake over all the spacies was maintained throughout most of the year by its morphological leaf properties. low leaf thickness, high chlorophyll contents. Besides, Cistus shed most of its leaves before summer, thus reducing its evaporative surface.
Keywords: ARBUTUS UNEDO L; CISTUS INCANUS L; leaf area index

Canopy structure within a Quercus ilex forested watershed: variations due to location, phenological development, and water availability - Sala, A; Sabate, S; Gracia, Carlos; Tenhunen, J D (Trees-Structure and Function, 1994)
Spatial and temporal changes in canopy structure were studied in 1988 and 1989 in a Mediterranean Q u e r c u s ilex forest in north-eastern Spain. Due to differences in precipitation patterns the 1989 growing season was drier than the 1988 growing season. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a watershed (ridge top at 975 m, and valley bottom at 700 m). At both sites, similar inter-annual changes in canopy structure were observed in response to differences in water availability. Samples harvested in the upper 50 cm of the canopy during 1989 exhibited a de- crease in both average leaf size and the ratio of young to old leaf and stem biomass relative to samples obtained in 1988. At the whole canopy level, a decrease in leaf pro- duction efficiency and an increase in the stem to leaf bio- mass ratio was observed in 1989. Temporal changes in canopy leaf area index (LAI) were not statistically sig- nificant. Average LAI values of Q. ilex at the two sites were not significantly different despite differences in tree stature and density (4.6 m 2 m -2 at the ridge top, and 5.3 m 2 m -2 at the valley bottom). Vertical distribution of leaves and stems within the canopy was very similar at the two locations, with more than 60% of the total LAI in the uppermost metre of the canopy. The possible significance of such an LAI distribution on the canopy carbon budget is discussed.
Keywords: Canopy structure; leaf area index; Mediterranean sclerophylls; Quercus ilex; water deficit